Burkina Faso : Request for a Three-Year Arrangement Under the Extended Credit Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2018)
This paper discusses Burkina Faso's Request for a Three-Year Arrangement Under the Extended Credit Facility (ECF). The program aims to maintain macroeconomic stability while promoting sustainable and inclusive growth. Under the program, fiscal space for priority security, social, and investment spending would be supported by strengthening revenue mobilization and containing current spending, especially on wages. Efforts to improve investment selection and execution would achieve more with the resources available. Prudent public financial and debt management along with energy sector reforms would ensure fiscal sustainability and mitigate fiscal risks. Structural reforms would improve the business environment and promote diversification. The IMF staff supports the authorities' request for an ECF arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet